1995
DOI: 10.7326/0003-4819-122-2-199501150-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Irritable Bowel Syndrome: Long-Term Prognosis and the Physician-Patient Interaction

Abstract: When diagnosed according to current criteria, IBS is associated with a good prognosis and the diagnosis is unlikely to be changed to that of an organic disease during follow-up. A positive physician-patient interaction may be related to reduced use of ambulatory health services by patients with IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
151
0
19

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(174 citation statements)
references
References 0 publications
4
151
0
19
Order By: Relevance
“…Similar results have been presented in other studies [41] who reported that well informed patients were associated with fewer follow-up visits. Apart from increased knowledge, the characteristics of the symptoms as well as their duration may also influence the patients' need of consultations [2,26].…”
Section: Discussionsupporting
confidence: 91%
“…Similar results have been presented in other studies [41] who reported that well informed patients were associated with fewer follow-up visits. Apart from increased knowledge, the characteristics of the symptoms as well as their duration may also influence the patients' need of consultations [2,26].…”
Section: Discussionsupporting
confidence: 91%
“…These findings support prior observations, such as those of Owens and colleagues who noted that a positive physician-patient interaction was associated, in the long term, with fewer return visits to the clinic for IBS 2 and an uncontrolled study, also from the Mayo clinic, that demonstrated, over a 6-month follow-up period, that an education class reduced symptoms and enhanced some health-promoting behaviours. 3 Apart from such shortcomings as the location of the study in a tertiary referral centre and relatively brief nature of the follow-up, what the Labus study cannot tell us is why their approach worked and, specifically, which of the elements of the programme was most beneficial.…”
supporting
confidence: 81%
“…However, in most cases the absolute differences in demographic data between those undergoing colonoscopy and providing complete symptom data and those who did not undergo colonoscopy were modest. We did not perform longitudinal follow-up to ensure that an organic diagnosis was not missed in individuals who met the reference standard for IBS, although previous studies have suggested that a diagnosis of IBS is unlikely to be revised during extended follow-up, 33 despite repeated investigation. 34 The reference standard included symptom data from the questionnaire, which may have led to an overestimation of the accuracy of the Rome III criteria.…”
Section: Discussionmentioning
confidence: 99%